Echocardiographic Changes and Long-Term Clinical Outcomes in Pediatric Patients With Pulmonary Arterial Hypertension Treated With Bosentan for 72 Weeks: A Post-hoc Analysis From the FUTURE 3 Study - Maurice Beghetti; Maurice Beghetti; Rolf M. F. Berger; Damien Bonnet; Simon Grill; Catherine Lesage; Jean-Christophe Lemarie; D. Dunbar Ivy (Frontiers Media S.A., 2021)
FormUlation of bosenTan in pUlmonary arterial hypeRtEnsion (FUTURE) 3 was a 24-week open-label, prospective, and randomized phase 3 study that assessed the pharmacokinetics of bosentan 2 mg/kg b.i.d. or t.i.d. in children with pulmonary arterial hypertension (PAH). We report findings from a post-hoc analysis that explored the prognostic value of echocardiographic changes during FUTURE 3 in relation to clinical outcomes observed during the 24-week core study and 48-week extension. Patients aged ≥3 months to <12 years (n = 64) received oral doses of bosentan 2 mg/kg b.i.d. or t.i.d. (1:1) for 24 weeks, after which they were eligible to enter the extension with continued bosentan administration. Echocardiographic evaluations were performed at baseline, Week 12, and 24 of the core study via central reading, and analyzed post-hoc for correlation with clinical outcomes (time to PAH worsening, time to death, and vital status). Sixty-four patients were randomized in the core study [median (IQR) age 3.8 (1.7-7.8) years]; and 58 patients (90.6%) entered the 48-week extension. Most of the patients (68.8%) were receiving ≥1 PAH medication at baseline. Echocardiographic changes during the core study were small but with high variability. There were statistically significant associations at Week 24 between worsening of the parameters, systolic left ventricular eccentricity index (LVEIS) and E/A ratio mitral valve flow, and the outcomes of time to death and time to PAH worsening. Additional studies that utilize simple and reproducible echocardiographic assessments are needed to confirm these findings and subsequently identify potential treatment goals in pediatric PAH.